The utility of occlusion of the pulse oximeter trace in the estimation of systolic blood pressure during spinal anaesthesia for caesarean section: the effect of body mass index - Samuel, Theresa (Department of Anaesthesia, 2017)
Background: We compared the accuracy and precision of estimation of the systolic blood pressure (SBP) by disappearance of the pulse oximeter trace (DOT), with noninvasive blood pressure (NIBP) measurement, across the range of body mass index (BMI), during spinal anaesthesia (SA) for caesarean section (CS). Methods: Three groups of 25 parturients were recruited, with BMI of < 30- (Group 1), 30-40- (Group 2), and > 40 kg/m2 (Group 3) respectively. SBP was measured using the DASH® 3000 monitor (GE Health Care, UK) NIBP monitor, placed on the same arm as the pulse oximeter probe. Estimations of SBP were done before- and 5 minutes after induction of SA, during cuff inflation and deflation. The times taken for the estimations and the actual NIBP measurements were noted. Bland and Altman analysis was performed and the correlation coefficient estimated. Results: Concerning the most clinically relevant estimation, namely SBP during inflation post-SA: For Groups 1, 2 and 3, r = 0.56, 0.74 and 0.91; bias = -0.4, -2.9 and 0.8 mmHg, and limits of agreement = -27.7 to 26.9, -27.7 to 21.9 and -15.9 to 17.5 mmHg respectively. The mean (SD) time required for estimation of the SBP during inflation post- SA was 7.5 (1.1) s, 11.8 (3.8) s and 16.8 (4.2) s in the Groups 1, 2 and 3 respectively. The mean (SD) time required for measurement of post-SA SBP during inflations in Groups 1, 2 and 3, was 30.3 (13.1) s, 41.3 (10.2) s and 49.8 (14.6) respectively. In the post-SA period, mean time saved by estimating SBP during inflation was approximately 28.5 seconds, compared with 9 seconds during deflation. The time saved in Groups 1, 2 and 3 was 22.8 (13.2) s, 30.0 (11.6) s and 33.0 (15.6) s respectively. In the BMI > 40 kg/m2 group, the percentage error is ±13% of the mean systolic blood pressure observed, and the absolute error is ±16 mmHg, compared to ±27 mmHg in the normal BMI group. Conclusion: Post-SA estimation of SBP during cuff inflation in morbidly obese patients is more accurate and precise than in the other BMI Groups. Time to estimation is shorter than measurement by a clinically relevant period (33 s). This should improve patient safety in morbidly obese parturients.